The Effects of Personal Photographs towards Students’ Writing Ability - Wulandari, Ratih Ayu; Safira, Meli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2021)
The aim of this research was to explore the effects of using students’ personal photographs towards students’ writing ability at the eighth grade students of SMPN 3 Pandeglang, Banten. This is a quantitative research with Quasi-Experimental design method. In this study, the researcher used essay writing tests as the instrument. The results of the study showed that: (1) The results of the pre-test t-count 2.426 > t-table 2.038 or H1 was accepted and H0 was rejected. It means that there were differences in the writing skills between the control class and the experimental class; (2) The results of the post-test t-count 7.831 > t-table 2.038 or H1 was accepted and H0 was rejected. It means that there were significant differences in the writing skills between the control class and the experimental class after being treated by using students’ personal photographs as the learning media. Hence, it could be concluded that the personal photographs gave significant and influential effects towards students’ writing ability at the eighth grade students of SMPN 3 Pandeglang, Banten. Personal photographs could be considered as instructional media causing students’ interest in learning recount text since they provide visual media that allowed them to recall their memories as they were.